Pengaruh Self Efficacy, Kompetensi, Remunerasi, Kepemimpinan dan Komunikasi terhadap Kinerja Karyawan melalui Organization Citizenship Behaviour - Erwin Sunanto; Suwandi Suwandi; Ahmad Hanfan (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
The problem that occurs at PT Hamana Works Indonesia is that the employee's performance has not been maximized, which is indicated by the fact that there are still many employees who use their leave rights from what has been stipulated. The research was conducted by collecting data by using a questionnaire on all employees with a total of 62 employees as respondents. Data from 2019 to 2020 shows an increase in employees using leave entitlements beyond the stipulated and reaching 50% in 2020. Researchers conducted tests using the SEM (Structural Equation Modeling) Partial Least Square or SEM PLS approach using tools in the form of statistical software, namely Smart pls. The results of the study are self-efficacy does not have a significant impact on employee performance, competence does not have a significant impact on employee performance, remuneration does not have a significant impact on employee performance, leadership has a significant effect on employee performance, communication has no significant effect on employee performance, Organizational citizenship behaviors have a significant effect on performance employees, self-efficacy has a significant effect on OCB, competence has a significant effect on OCB, remuneration has no impact on OCB, leadership has no impact on OCB, communication has a significant effect on OCB, self-efficacy through OCB has a significant effect on performance, competence through OCB has no significant effect on performance , remuneration through OCB has no significant effect on employee performance, leadership through OCB has no significant effect on performance and communication has a positive effect through OCB on app employee performance. Researchers suggest companies to improve leadership, OCB, competence, communication and self-efficacy for employees.